Propagation of yellow passion fruit seedlings by cutting, grafting and seeds under salt stress (Bioscience Journal, 2022)
Salinity is one of the most limiting abiotic stresses in the global agricultural sector. The objective of this study was to evaluate the effect of irrigation water salinity on the initial development of P. edulis Sims. seedlings propagated by seeds, grafting and cuttings. Treatments were distributed in a completely randomized design, in a 5 x 3 factorial arrangement, corresponding to 5 levels of irrigation water electrical conductivity (0.3 - control, 1.8, 3.3, 4.8, and 6.3 dS m-1) and 3 propagation methods (seeds, cuttings and grafting), with four replicates and one plant per plot. Fifty days after the imposition of treatments with saline water, plant height, number of leaves, stem diameter, total chlorophyll, stomatal conductance, relative leaf water content, total water consumption, dry matter of root, shoot and total, root length and root volume were evaluated. The increase in water salinity affected with greater intensity the growth and development variables (height, total dry matter and root volume of the plant) and the physiological characteristics (stomatal conductance) of the species Passiflora edulis, regardless of the method of propagation. Seedlings propagated by grafting showed better development compared to the other propagation methods (seeds and cuttings). The interaction between the propagation methods and water salinity affected seedlings propagated by seeds and cuttings with greater intensity.